Over-lexicalization and Under-lexicalization of Physical Violence Expression in Laut Bercerita and Its Translation by Leila S. Chudori - Amalia, Friska; Munandar, Aris (Institut Agama Islam Negeri (IAIN) Kendari, 2024)
Although research on lexicalization has been extensively documented, little is known about over- and under-lexicalization in translation.